'La Vida Normal': Young people adapting to Type 1 diabetes in Bolivia. (September 2021) - Souris, Katherine J; Caballero Gonzales, Maria del Carmen; Barrington, Clare; Klatman, Emma L; Anderson, Barbara J; Duarte, Elizabeth; Middlehurst, Angela C; Nostas, Miriam C; Ogle, Graham D
Objectives: To identify challenges and coping strategies of young people with Type 1 diabetes (T1D) and their families in Bolivia through qualitative analysis of interviews with beneficiaries of Centro Vivir con Diabetes (CVCD), a diabetes health center supported by the International Diabetes Federation Life for a Child (LFAC) program. Methods: Eighteen young people aged 14–33 and at least one caregiver participated in semi-structured interviews in five cities in Bolivia from May to June 2016. Interviews were recorded, transcribed, and analyzed using inductive thematic analysis. Results: Participants described needing guidance at diagnosis and facing stigma in communities. Young people expressed that life with T1D was 'la vida normal' (a normal life), although interpretations of normalcy varied. For some, 'la vida normal' meant resistance to T1D; for others it indicated acceptance. Discussion: Access to interdependent spheres of support allowed young people to form a new normal around T1D. Receiving supplies through the CVCD/LFAC partnership maintained family connection to clinical care, CVCD education helped families share in T1D management, and peer support mitigated stigma for young people. Programs like CVCD that combine supply-based aid with clinical education for whole families, create effective support for young people with T1D in low- and middle-income countries.